Removal of Seminal Plasma Enhances Membrane Stability on Fresh and Cooled Stallion Spermatozoa. Issue 1 (24th April 2012) - Barrier‐Battut, I; Bonnet, C; Giraudo, A; Dubois, C; Caillaud, M; Vidament, M
Contents Fertility is reduced after semen cooling for a considerable number of stallions. The main hypotheses include alterations in plasma membrane following cooling and deleterious influence of seminal plasma. However, interindividual variability is controversial. We hypothesized that the removal of seminal plasma could enhance motility in some 'poor cooler' stallions, but could also affect, negatively or positively, membrane quality in some stallions. This study examined the effect of centrifugation, followed or not by removal of seminal plasma, on parameters indicating semen quality after 48 h at 4°C: motility, plasma membrane integrity as evaluated by hypo‐osmotic swelling test, acrosome integrity and response to a pharmacological induction of acrosome reaction using ionophore A23187. Sixty‐six ejaculates from 14 stallions were used, including stallions showing high or low sperm motility after cooled storage. Centrifugation without removal of seminal plasma did not affect sperm parameters. Removal of seminal plasma did not affect motility, but significantly stabilized sperm membranes, as demonstrated by a higher response to the osmotic challenge, and a reduced reactivity of the acrosome. Moreover, for the same semen sample, the response to an induction of acrosome reaction was significantly higher when the induction was performed in the presence of seminal plasma, compared with the induction in the absence of seminal plasma. This was observed both for fresh and cooled semen. When the induction of acrosome reaction with ionophore A23187 is used to evaluate sperm quality, care must therefore be taken to standardize the proportion of seminal plasma between samples. For the 10 stallions serving at least 25 mares, the only variable significantly correlated with fertility was motility. The influence of membrane stabilization regarding fertility requires further investigations.